ANTHROPOLOGICAL ASPECT OF THE NATURE OF THE STATE - Volodymyr V. Khmil; Tetiana V. Khmil (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of the research is to find new ways and methods to substantiate ethic and moral standards as the basis of civil interference into the life of the state. The role and place of the state in social, political and spiritual transformations are not always considered due to the crisis of certain social theories and models of state development. Methodology of the research is based on comparative, historical and logical methods. The applied investigation methods enable to reveal and analyze specific models related to anthropological aspect in social relations used in definite types of state formations in order to find that dynamic outlook on future and personal fulfilment of a human.The scientific novelty is in concept to broaden the representation of freedom evolution of a human in different historic types of states. Comparative analysis of state development and the place of human freedom in them helps firstly, conceive anthropological determinant, the one that gradually places under control state institutions which are necessary for humanization of external conditions of human beings and secondly, find out possible directions of state development and freedom for human activity. Conclusions. Understanding and reasoning of paradigm systems development based on moral constituent of the state is an anchoring point for the reforming state towards human values. The state developing on moral human principles gravitates towards its self-destruction.ible directions of state development and freedom for human activity. Conclusions. Understanding and reasoning of paradigm systems development based on moral constituent of the state is an anchoring point for the reforming state towards human values. The state developing on moral human principles gravitates towards its self-destruction.